2010
DOI: 10.1002/jctb.2441
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study on ethanol production using Saccharomyces cerevisiae ITV‐01 yeast isolated from sugar cane molasses

Abstract: BACKGROUND: Bio-ethanol production from renewable sources, such as sugar cane, makes it a biofuel that is both renewable and environmentally friendly. One of the strategies to reduce production costs and to make ethanol fuel economically competitive with fossil fuels could be the use of wild yeast with osmotolerance, ethanol resistance and low nutritional requirements. The aim of this work was to investigate the kinetics of ethanol fermentation using Saccharomyces cerevisiae ITV-01 yeast strain in a batch syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 26 publications
6
30
2
1
Order By: Relevance
“…Once hexoses are available, the strain shows a glucose preference over fructose (data not shown) also previously reported for Saccharomyces cerevisiae [29,30]. Hexose presence in the medium controls plasmatic membrane transport rate and can also affect catabolic repression [18,20]. However, these differences between the preferences of the type of sugar consumed can vary depending on several factors: strain type, initial substrate concentration, nitrogen availability, all of which are suspected to affect fructose more than glucose consumption.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Once hexoses are available, the strain shows a glucose preference over fructose (data not shown) also previously reported for Saccharomyces cerevisiae [29,30]. Hexose presence in the medium controls plasmatic membrane transport rate and can also affect catabolic repression [18,20]. However, these differences between the preferences of the type of sugar consumed can vary depending on several factors: strain type, initial substrate concentration, nitrogen availability, all of which are suspected to affect fructose more than glucose consumption.…”
Section: Resultsmentioning
confidence: 50%
“…S. cerevisiae ITV-01 is a wild-type strain isolated from sugarcane molasses exhibiting interesting characteristics for ethanol production, such as osmotolerance and ethanol resistance in a synthetic medium. The best conditions reported for ethanol production were pH 3.5, 150 g L -1 glucose, a temperature of 30°C, and 81 g L -1 ethanol tolerance [16][17][18]. Several factors can affect cell growth and ethanol production; carbon source, inoculum size, initial sugar concentration, pH, temperature and oxygen supply are the most important [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ortiz-Muñiz et al (33) reported that a yeast extract stimulates glucose consumption because the important cofactors biotin and riboflavin are present, and high yeast extract concentrations do not affect either S. cerevisiae growth or fermentative ability.…”
Section: Resultsmentioning
confidence: 97%
“…41,42 These nitrogen sources also enhance sugar utilization for increased ethanol yield. [42][43] Yeast extract also supplies cofactors such as biotin and riboflavin for enhancement of ethanol yield. 43 Nevertheless, the use of yeast extract adds significant expense to the medium used in our study, and further work might focus on finding lower cost substitutes that still provide the same benefits.…”
Section: Medium Compositionmentioning
confidence: 99%